Phenomenological Study on Aging of Women in 40's and 50's: Applying the Parse's Theory - Ju Eun Hong; Keong Jin Do; Ru Mee Ha; Seok Bun Jeon; Sung Soun Hur; Eun Kwang Yoo (Korean Society of Women Health Nursing, 2014)
PURPOSE: This study was done to explore the essence and meaning of the experience of 'aging,' as a process of 40's and 50's women in Korea by applying the Parse's Human Becoming theory (2002). METHODS: Data was collected from February to April, 2013, using the phenomenological research method. Data was collected through in-depth informal interview and analyzed following Colaizzi method. After IRB permission and informed consent from the participants, all interviews were recorded with MP3 recorder and transcribed for analysis. RESULTS: Data analysis revealed 112 of meanings, 33 key subject words, 8 subject phrases, and 4 categories. The main themes were elaborated as 'going down' ('Being changed of body and mind', 'Being considered on my identity'), 'going up' ('Being expanded of productive role', 'Being transcendent multi-dimensionally'), 'pausing' ('Becoming more thoughtful about family', 'Looking back'), 'going forward again' ('Age is just a number, 'Contemplating of life and death'). Experiences in aging among women in 40's and 50's enlightened with Parse's theory of Human Becoming in terms of 'going down', 'going up', 'pausing', 'going forward again' appeared simultaneously, rather than consecutively. CONCLUSION: Women in 40's and 50's require holistic nursing intervention with physical, psychological, socio-economical, and spiritual aspects, rather than focusing on problematic physical symptom relief and prevention of further conditions. It is recommended to develop various nursing intervention considering on different environment, type of experience, and level of human becoming, individually.